Microbiological analysis of urinary calculi: A study from a tertiary care hospital of Eastern India - Kumar, Ashutosh; Kunal,; Manish Kumar,; Kumar Aamresh,; Hassan, Ashif Ali; Anupma, Anjoo (Asian Journal of Medical Sciences, 2023)
Background: Among various renal pathology, urolithiasis among patients of urinary tract infections (UTIs) forms a major group. The pathophysiology of such patients varies from the group of urolithiasis patients without infection. Aims and Objectives: The current study was planned and conducted to find out the bacteriological profile of urinary calculi among patients of UTI. Materials and Methods: A descriptive study was conducted by the Department of Microbiology and Surgery of JLNMC, Bhagalpur, Bihar. A total of 100 patients were enrolled in the study, having urinary calculi who either visited the outpatient department or who were admitted at the hospital for planned procedure for removal of stone between January 2021 and December 2021. Results: Male predominance was noted with a mean age of presentation at 44.3 years. 67% of the patients had some or the other symptoms of UTI, most common symptom being excruciating groin pain. Recurrent episodes of UTI were noted among female patients. Bacterial growth on culture was obtained from the urine samples of 46 patients. Escherichia coli were the most common isolated organism. Most common type of stone was a mixed type of stone formed by calcium oxalate and calcium phosphate followed by struvite stones and uric acid stones. Conclusion: Various factors of clinical significance among patients of urolithiasis and UTI are gender, age, and clinical symptoms. Gram-negative bacilli are the most common bacteria found in UTIs in patients with urolithiasis.